[Image 21] - Smith, Captain Sir William [?ob. 1732] (My University, 1800)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of Sir Wm: Smith's lodging & accommodation while erecting & building the naval signal station at Fannat Point in February & part of March as drawn by himself!!
Keywords: Fannat Point; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810